2022
DOI: 10.3390/brainsci12091120
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization and Prognostic Value of TPM4 and Its Correlation with Epithelial–Mesenchymal Transition in Glioma

Abstract: Tropomyosin 4 (TPM4) has been reported as an oncogenic gene across different malignancies. However, the role of TPM4 in glioma remains unclear. This study aimed to determine the clinical characterization and prognostic value of TPM4 in gliomas. Transcriptome expression and clinical information were collected from the CGGA and TCGA datasets, which included 998 glioma patients. ScRNA-seq data were obtained from CGGA. R software was utilized for statistical analyses. There was a positive correlation between TPM4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…There are four tropomyosin (TPM) genes, namely TPM1, TPM2, TPM3, and TPM4, in mammals. In recent years, the abnormal expression of TPM4 was investigated in multiple malignancies, invasive breast cancer ( 7 ), colon cancer ( 8 ), glioma ( 9 ), hepatocellular carcinoma ( 10 ), lung cancer ( 11 ), and ovarian cancer ( 12 ). TPM4 is a crucial intermediary in different human malignancies, but the association between the function of TPM4 and GC is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four tropomyosin (TPM) genes, namely TPM1, TPM2, TPM3, and TPM4, in mammals. In recent years, the abnormal expression of TPM4 was investigated in multiple malignancies, invasive breast cancer ( 7 ), colon cancer ( 8 ), glioma ( 9 ), hepatocellular carcinoma ( 10 ), lung cancer ( 11 ), and ovarian cancer ( 12 ). TPM4 is a crucial intermediary in different human malignancies, but the association between the function of TPM4 and GC is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…TPM4 expression is of clinical significance, has prognostic value, and is related to immune infiltration in pancreatic cancer ( 14 ). TPM4 is upregulated and related to the malignant characteristics of gliomas, possibly via epithelial-mesenchymal transition ( 9 ). In our previous study, TPM4 was found to function as an oncogene that stimulates the proliferation of cells and prevents the death of cells by apoptosis both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied the role of Tropomyosin 4 (TPM4) (an oncogenic gene known to be involved in many malignancies) in 998 glioma patients and suggest that TPM4 is significantly correlated with more malignant characteristics of gliomas, potentially through involvement in epithelial-to-mesenchymal transition with a worse prognosis. It is an original and elegant study on a great number of patients [ 13 ].…”
mentioning
confidence: 99%